APPROACHES TO AUTOMATIC CHECKING OF PRACTICAL ASSIGNMENTS IN MOOCS AND ONLINE LEARNING - Buravov, Alexey; Нуржан, Дузбаев (МЕЖДУНАРОДНЫЙ ЖУРНАЛ ИНФОРМАЦИОННЫХ И КОММУНИКАЦИОННЫХ ТЕХНОЛОГИЙ, 2022)
One of the most important components of distance learning for software developers is practice. For effective learning and scaling, one needs the ability to check student’s code automatically. This paper presents an actual overview of existing state-of-the-art online e-learning platforms, Massive Open Online Courses (MOOCs), and other online learning services and solutions with automatic checking of students’ practical assignments. It also provides an extensive theoretical framework for automatic compilation, code validation, architecture, scalability, and fault tolerance.